2021
DOI: 10.1002/art.41507
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Urinary Epidermal Growth Factor and Renal Prognosis in Lupus Nephritis

Abstract: Objective To evaluate the role of urinary epidermal growth factor (EGF) as a biomarker of chronic kidney damage in lupus nephritis (LN). Methods A proteomics approach was used to identify urinary EGF as a biomarker of interest in a discovery cohort of patients with LN. The expression of urinary EGF was characterized in 2 large multiethnic LN cohorts, and the association between urinary EGF levels at the time of flare and kidney outcomes was evaluated in a subset of 120 patients with long‐term follow‐up data. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 40 publications
(74 reference statements)
0
24
0
Order By: Relevance
“…As far as we know, there has been only one study evaluating the role of EGF in LN. Mejia-Vilet et al evaluated the relationship of urinary EGF to renal histology and long-term change in GFR in US and Mexican patients with LN [ 35 ]. They found that EGF correlated with chronicity index and predicted long term GFR levels, but did not correlate with activity index.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, there has been only one study evaluating the role of EGF in LN. Mejia-Vilet et al evaluated the relationship of urinary EGF to renal histology and long-term change in GFR in US and Mexican patients with LN [ 35 ]. They found that EGF correlated with chronicity index and predicted long term GFR levels, but did not correlate with activity index.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Mejia‐Vilet and colleagues (11) is a pilot study that validates the urinary EGF level as a biomarker for kidney reserve in LN. Although the urinary EGF level is not specific for SLE, it may be a surrogate marker for residual nephron mass in patients with kidney diseases.…”
mentioning
confidence: 92%
“…In this same issue of Arthritis & Rheumatology , Mejia‐Vilet et al (11) reported on their study of the relationship between the urinary epidermal growth factor (EGF) level and progression of chronic kidney disease in several cohorts of patients with LN. This biomarker was identified by MS‐based proteomics screening in a discovery cohort and validated by immunoblotting and ELISA.…”
mentioning
confidence: 99%
“…uEGF levels correlate with intrarenal mRNA expression of EGF on kidney biopsy and inversely correlate with the degree of interstitial fibrosis and tubular atrophy ( 16 , 19 , 20 ). Theoretically, already at an early stage in the disease, a decrease in uEGF could thus precede glomerular deterioration visualized on kidney biopsy ( 15 , 19 , 21 ). Tubular injury is closely linked to progression in glomerular nephropathies ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, tubular proteins such as uEGF are potentially better predictive markers for progression of glomerular damage and renal deterioration than proteinuria and albuminuria ( 17 ). Particularly for uEGF, over the last few years, increasing evidence highlights its added value in predicting kidney deterioration in many disease entities such as systemic lupus disease ( 21 ), diabetes mellitus ( 23 ), but also in IgA nephropathy ( 15 , 24 ), and other chronic kidney diseases ( 17 ) in adults. Specifically in children, recent reports illustrated the prognostic capacities of uEGF regarding renal decline in pediatric patients with chronic kidney disease ( 25 ), Alport syndrome ( 20 ), and nephrotic syndrome ( 19 ).…”
Section: Introductionmentioning
confidence: 99%